Poziom akumulacji a zasoby gospodarstw rolniczych - Gołębiewska, Barbara (An Accumulation Level and Farm Resourses, 2005)
In this paper factors having significant influence on capital accumulation in agricultural farms in Poland are described. Analysis which has beech done shows that in almost 30 per cent of farms another analysis of the negative accumulation level was observed. Significantly important correlation with positive accumulation was noticed for such factors as area of agriculture land level of employment as well as higher level of education.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 256-261